TRADE IN SERVICES AND ECONOMIC SECURITY OF STATE: CRITERIA OF INTERCONNECTION UNDER CONDITIONS OF GLOBALIZATION - Nataliya, Iksarova; Turaieva, Tetiana (European Scientific Journal, ESJ, 2014)
The influence of trade in services on state of economic security is investigated at the article. The methodology of estimation of influence of trade in services on indicators of macroeconomic and budgetary security is proposed. On basis of analyze, criteria of interconnection between international trade in services and economic security are grounded.